Surfactant-free synthesis of a novel octahedral ZnFe2O4/graphene composite with high adsorption and good photocatalytic activity for efficient treatment of dye wastewater. Issue 8 (1st June 2020) - Ai, Jianping; Hu, Liling; Zhou, Zehua; Cheng, Lihong; Liu, Wenjin; Su, Kaiyu; Zhang, Ruibo; Chen, Zhiqin; Li, Wenkui
Abstract: Recently, significant effort has been made toward the development of graphene-based visible-ligh-responsive photocatalysts and their application to dye wastewater treatment. Herein, a series of octahedral ZnFe2 O4 /graphene (ZnFe2 O4 -G) nanocomposites were synthesized using a one-pot solvothermal reaction without the need of a surfactant as novel bifunctional materials exhibiting both high adsorption and good visible-light-responsive photocatalyst properties. The crystal structure, morphology and photocatalytic degradation properties, as well as adsorption behavior, of the octahedral ZnFe2 O4 /graphene composites were investigated in detail. The adsorption capacity and UV–vis spectrometry results indicate that the dye removal efficiency over the samples followed the order of: methylene blue (MB) > rhodamine B (RhB) > methyl orange (MO). The ZnFe2 O4 -G materials exhited enhanced photocatalytic degradation properties for cationic dyes (MB and RhB) compared to those for the anionic dye (MO). In addition, the experimental results indicate that the ZnFe2 O4 -G materials can decompose H2 O2 in the visible-light photocatalytic process to form hydroxyl radicals (OH), which are mainly responsible for the photodegradation of the organic contaminants.